A Feasibility Study of a Multifaceted Walking Intervention to Maintain the Functional Mobility, Activities of Daily Living, and Quality of Life of Nursing Home Residents With Dementia. Issue 4 (July 2020) - Chu, Charlene H.; Puts, Martine; Brooks, Dina; Parry, Monica; McGilton, Katherine S.
Abstract: Purpose: The aim of the study was to evaluate the feasibility, acceptability, and efficacy of a multifaceted walking intervention (MWI) aimed to maintain the functional mobility, activities of daily living function, and quality of life of long-term care home residents with dementia. Design/Methods: A quasiexperimental time-series design was used. The 4-month intervention provided one-on-one walking 2–4 days a week, guided by an individualized communication care plan and interviews with collaterals and staff. Results: The MWI was feasible based on high recruitment and adherence rates (86% and 94%, respectively) and highly acceptable to stakeholders. Residents ( n = 25) showed significant improvements after the intervention: Timed Up-and-Go (−8.85 seconds, p = .00), Two-Minute Walk Test (27.47 m, p = .00), Functional Independence Measure (0.72, p = .00), and Alzheimer's Disease-Related Quality of Life (2.44, p = .05). Conclusion: The MWI was feasible and improved functional mobility compared to usual care. Clinical Relevance: Physical activity delivered with a person-centered care was feasible and may be beneficial to mitigate decline in long-term care home residents with dementia.